Perbandingan Aktivitas Antibakteri pada Berbagai Konsentrasi Ekstrak Bunga Telang (Clitoria ternatea L.) terhadap Staphylococcus aureus: Suatu Tinjauan Naratif - Anisa Safitri; Atri Sri Ulandari; Afriyani Afriyani; Zulpakor Oktoba (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Introduction: Staphylococcus aureus infection remains a major health problem due to the increasing resistance to conventional antibiotics. Butterfly pea flower (Clitoria ternatea L.) contains bioactive compounds with potential antibacterial properties. This study aimed to evaluate the antibacterial effectiveness of butterfly pea flower extract and to assess the effect of extract concentration variation against Staphylococcus aureus. Method: This study employed a narrative literature review by searching articles from Google Scholar (1,130 articles), PubMed (2 articles), and ScienceDirect (235 articles) published between 2015 and 2025. Articles were selected based on inclusion criteria, namely experimental studies using Staphylococcus aureus as the test bacterium and reporting variations in butterfly pea flower extract concentrations. Exclusion criteria included review articles or proceedings, studies without inhibition zone data, studies not using Staphylococcus aureus, and articles not available in full text. Articles meeting the criteria were analyzed descriptively and comparatively (n = 9 articles). Discussion: Analysis of the nine selected studies indicated that increasing concentrations of butterfly pea flower extract were associated with larger inhibition zones against Staphylococcus aureus. Variations in results were influenced by solvent type, extraction methods, and antibacterial testing techniques. Conclusion: Butterfly pea flower extract demonstrated consistent antibacterial activity against Staphylococcus aureus, particularly at higher concentrations, suggesting its potential development as a natural antibacterial active ingredient.